Παρατηρήσεις στο «Οδοιπορικόν» του Κωνσταντίνου Μανασσή. - ΧΡΥΣΟΓΕΛΟΣ, Κωνσταντίνος (Byzantina Symmeikta, 2013)
<!--[if gte mso 9]> Normal 0 false false false EL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> SOME OBSERVATIONS ON CONSTANTINE MANASSES' ITINERARY. ΤHE MOTIFS OF THE TEMPEST AND THE DRAUGHT The purpose of this paper is to present and examine two key-motifs - that of the tempest and the drought-in Constantine Manasses’ Itinerary -a 12th century poem reciting the narrator’s dreadful experiences during his trip to Palestine, on an official mission by emperor Manuel Komnenos In the four chapters of the poem, these two motifs are treated in a literate, as well as a figurative way (as far as the tempest is concerned, a topos in the 12th century literature), in order to convey the narrator’s own misfortunes and woes, including the two illnesses he suffered from, while residing in Tyros and Cyprus, respectively. Furthermore, the presence and the combination of the aforementioned motifs hold a significant position in the macrostructure of the Itinerary. Among other things, the study of the way Manasses uses these motifs intents to highlight the poet’s skilful art.